Effectiveness of Cognitive-Behavioral Therapy on Perceived Pain and Sleep Quality in Patients with Fibromyalgia - Sadighi, Anbar; Shokrgozar, Alireza; Sodagar, Sheida; Bahrami-Hidaji, Maryam; Raeissadat, Seyed Ahmad (Psychology of Woman Journal, 2026)
Objective: The present study aimed to evaluate the effectiveness of cognitive-behavioral therapy (CBT) on perceived pain and sleep quality among patients with fibromyalgia. Methods and Materials: This research employed a quasi-experimental design with a pretest–posttest format, a control group, and a three-month follow-up period. The statistical population consisted of all patients with fibromyalgia who referred to the rehabilitation clinic of Modarres Hospital in Tehran during 2023–2024. Using purposive sampling, 45 participants were selected and randomly assigned to three equal groups of 15. Data were collected using the Pain Perception Questionnaire (McGill, 2009) and the Pittsburgh Sleep Quality Index (Buysse et al., 1989). The CBT intervention was conducted across 10 weekly sessions, each lasting 90 minutes. Participants in the control group did not receive any psychological intervention during this period. Data analysis was performed using descriptive statistics and mixed analysis of variance (ANOVA) with repeated measures. Findings: The findings indicated that CBT significantly reduced perceived pain (F = 107.539, η² = 0.349) and improved sleep quality (F = 190.376, η² = 0.427) in patients with fibromyalgia (p < .05). Conclusion: The results support the efficacy of cognitive-behavioral therapy in alleviating perceived pain and enhancing sleep quality among individuals with fibromyalgia. These findings underscore the importance of psychological and behavioral factors in the management of fibromyalgia and highlight the potential of CBT as an effective complementary intervention to improve patients’ overall functioning and quality of life.